2019
DOI: 10.1016/j.neurobiolaging.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Aged rats with preserved memory dynamically recruit hippocampal inhibition in a local/global cue mismatch environment

Abstract: Similar to elderly humans, aged outbred Long Evans rats exhibit individual differences in memory abilities, including a subset of aged rats that maintain memory function on par with young adults. Such individuals provide a basis for investigating mechanisms of resilience to age-related decline. The present study examined hippocampal gene expression in young adults and aged rats with preserved memory function under behavioral task conditions well-established for assessing information processing central to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…Locations between 0-40% of the proximodistal length were defined as proximal CA3, 40-70% as intermediate CA3, and 70-100% as distal CA3 (Lu et al, 2015). The aged rats were pretested in the Morris water maze and categorized as learning impaired (AI) or learning unimpaired (AU) based on pre-determined learning index scores (Gallagher et al, 1993;Haberman et al, 2011;Branch et al, 2019) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Locations between 0-40% of the proximodistal length were defined as proximal CA3, 40-70% as intermediate CA3, and 70-100% as distal CA3 (Lu et al, 2015). The aged rats were pretested in the Morris water maze and categorized as learning impaired (AI) or learning unimpaired (AU) based on pre-determined learning index scores (Gallagher et al, 1993;Haberman et al, 2011;Branch et al, 2019) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…All rats were prescreened for spatial learning ability in the Morris water maze as previously described (Branch et al, 2019;Gallagher et al, 1993) prior to the implantation of recording electrodes. Briefly, all rats were trained for 8 days (3 trials per day) in the water maze to locate a submerged escape platform that remained at the same location in the tank.…”
Section: Subjects and Surgerymentioning
confidence: 99%
“…Indeed, other studies using this model of neurocognitive aging have shown that AU rats have enhanced postsynaptic synaptic inhibition in granule cells and enhanced tonic inhibition in CA1 pyramidal cells (Tran et al, 2018). Moreover, preserved cognitive performance in this study population is associated with increased task-induced expression of gene markers of synaptic inhibition across hippocampal subfields in AU rats compared to young adults (Branch et al, 2019).…”
Section: Discussionmentioning
confidence: 46%
“…This result indicated preserved recognition by the AU animals of spatial environmental change. The increase in scanning rate in the mismatch session was accompanied by similar increases in the activity of excitatory neurons in the hippocampus (Branch et al, 2019) and other cortical regions (Haberman et al, 2019) for both YG and AU rats, as measured by zif-268 expression. However, the expression of the inhibitory gene marker for the GABA-enzyme GAD1…”
Section: Discussionmentioning
confidence: 71%
“…was increased in the hippocampus in AU rats only (Branch et al, 2019). Because AI rats are known to have abnormally high levels of hippocampal activity (Wilson et al, 2003(Wilson et al, , 2004(Wilson et al, , 2005, which are correlated with poorer performance on the water maze (Haberman et al, 2017), Branch et al (2019) suggested that the increase in interneuron activity in the mismatch sessions in the AU rats may be a compensatory mechanism to limit hippocampal neuronal hyperexcitability in the mismatch session. This compensation presumably keeps the population activity level of hippocampal neurons in AU rats in the normal range displayed by YG rats.…”
Section: Discussionmentioning
confidence: 99%